Bioflocs Technology: Theory and Application in Intensive Aquaculture System - Ekasari, Julie (Jurnal Akuakultur Indonesia, 2009)
Bioflocs technology (BFT) is one of the developing technology in aquaculture which aimed to improve water quality and to enhance nutrient utilization efficiency. This technology is mainly based on the conversion of inorganic nitrogen in particular ammonia by heterotrophic bacteria into microbial biomass which further can be consumed by aquaculture organisms. The objective of this review is to discuss various aspect of BFT application in aquaculture including bioflocs formation process, technical requirement, bioflocs nutritional content and characterization techniques. Keywords: bioflocs, nitrogen, heterotrophic bacteria, ammonia, C/N ratio   ABSTRAK Teknologi bioflok (BFT) merupakan salah satu teknologi yang saat ini sedang dikembangkan dalam akuakultur yang bertujuan untuk memperbaiki kualitas air dan meningkatkan efisiensi pemanfaatan nutrient. Teknologi ini didasarkan pada konversi nitrogen anorganik terutama ammonia oleh bakteri heterotrof menjadi biomassa mikroba yang kemudian dapat dikonsumsi oleh organisme budidaya. Tujuan penulisan makalah ini adalah untuk memaparkan berbagai aspek dalam BFT termasuk proses pembentukan bioflok, persyaratan teknis, kandungan nutrisi bioflok dan teknik karakterisasinya. Kata kunci: bioflok, nitrogen, bakteri heterotrof, ammonia, rasio C/N